PREVALENCE OF ANAEMIA AMONG SCHOOLCHILDREN IN EASTERN SUDAN - E. Musa, Shams; ElSharief, Omer; Magzoub, Mamoun; Mohamed, Mohamed Ali (Gezira Journal of Health Sciences, 2010)
Background: Anaemia in children is a health problem particularly in developing countries, such as Kassala area, eastern Sudan. Methods: A total of 401 children from four primary schools in kassala were random simple stratified selected during a period of two months and prevalence of anaemia was estimated, clinically and by measuring haemoglobin concentration. Results: Clinical examination revealed anaemia in 373 of the students and haemoglobin estimations proved anaemia in 93% of the students enrolled in the study (Hb. less than 13.5 g/dl). Conclusion : The study showed high prevalence of anaemia among schoolchildren in the study area, so we recommend that more studies must be done in this area and the heath authorities may interfere by heath education and other interventional methods (e.g. provision of iron and folate).